2020
DOI: 10.3892/mmr.2020.11446
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑214 promotes the EMT process in melanoma by downregulating CADM1 expression

Abstract: Melanoma is a malignant skin cancer type associated with a high mortality rate, but its treatment is currently not ideal. Both microrna (mir)-214 and cell adhesion molecule 1 (cadM1) are differentially expressed in melanoma, but their role in this cancer type remains unknown. Therefore, the aim of the present study was to investigate the role of cadM1 and mir-214 in melanoma to identify novel targets for its treatment. The expression levels of cadM1 and mir-214 in cells were detected by reverse transcription-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…After culturing at 37°C for 24 h, cells on the underside of the membrane were fixed with 5% glutaraldehyde for 30 min at 4°C, and then stained with 0.5% crystal violet for 30 min at room temperature. Images were taken using an inverted light microscope (Leica, Germany) and invading cells in different areas were counted and analyzed using ImageJ software [ 29 ]. All experiments were repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…After culturing at 37°C for 24 h, cells on the underside of the membrane were fixed with 5% glutaraldehyde for 30 min at 4°C, and then stained with 0.5% crystal violet for 30 min at room temperature. Images were taken using an inverted light microscope (Leica, Germany) and invading cells in different areas were counted and analyzed using ImageJ software [ 29 ]. All experiments were repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…In melanoma, another miRNA molecule, miR-214, is prometastatic. MiR-214 silences cell adhesion molecule 1 (CADM1), a known tumor suppressor, thus leading to higher migration and invasion of melanoma cells and EMT promotion, in which miR-214 contributes to annoikis resistance and subsequently to extravasation [ 99 , 100 ]. The relevance of the miR-199/miR-214 cluster was also described in triple negative breast carcinoma (TNBC); however, in TNBC, the overexpression of miRNAs from the miR-199/miR-214 cluster leads to the inhibition of EMT, higher expression of epithelial markers E-cadherin and β-catenin, and decreased expression of the mesenchymal marker SNAIL2 (also known as SLUG) [ 101 ].…”
Section: Micrornas Involved In the Metastatic Cascadementioning
confidence: 99%
“…Wei et al [8] showed that RNF128 affects the EMT process of melanoma by acting on the ubiquitination of CD44 and CTTN in melanoma cells through the Wnt/β-catenin signaling pathway. Wang et al [31] showed that microRNA-214 downregulated CADM1 in melanoma cells, thereby promoting EMT progression in melanoma. Together, these results suggest that the development of melanoma may be favored by the promotion of cellular EMT.…”
Section: It Has Been Reported Previously Thatmentioning
confidence: 99%